Social media and anti-immigrant prejudice: a multi-method analysis of the role of social media use, threat perceptions, and cognitive ability - Ahmed, Saifuddin; Jaidka, Kokil; Chen, Vivian Hsueh Hua; Cai, Mengxuan; Chen, Anfan; Emes, Claire Stravato; Yu, Valerie; Chib, Arul (Frontiers in Psychology, 2024)
Immigration and immigrants are imminent in contemporary political and public discourse. Examining how people discuss immigrants online holds critical signals of public opinion, which can be triangulated with evidence from data collected from questionnaires, which offers insights into the psychological mechanisms underlying attitude formation. We report the findings from two studies that explore the aggregate-level expressive and individual-level informational use of social media in the context of attitudes toward immigrants. In Study 1, a computational text analysis of comments posted to Singaporean Facebook pages and other online forums suggests that when discussing immigrants, social media users were more likely to express negative emotions and mention economic threats, such as ‘jobs’ and ‘crime.’ Using the Integrated Threat Theory framework, Study 2 drills into individual-level informational use of social media, using primary survey data to test the relationships between cognitive ability, threat perceptions and negative emotions toward immigrant outgroups, and social media use. The findings complement Study 1 and show that individuals with higher social media use, and higher symbolic and realistic threat perception are more likely to exhibit anti-immigrant emotions. Symbolic and realistic threat perceptions positively mediated the relationship between social media use and anti-immigrant emotions. These effects are more pronounced for individuals with lower than higher cognitive ability.